Pengaruh Gaya Kepemimpinan Transformasional dan Beban Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada Bank Nagari - Viona Ramifa Reja; M. Afuan; Engla Desnim Silvia (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research aims to determine how much influence Transformational Leadership Style and Workload have on Employee Performance with Job Satisfaction as an Intervening Variable at Bank Nagari Main Branch. The data collection technique uses a questionnaire filled in by 67 employees as respondents. The analytical method used is Structural Equalition Modeling (SEM) with Partial Least Square (PLS).The results of data analysis conclude (1) Transformational Leadership Style has a positive and significant effect on Job Satisfaction. (2) Workload has a positive and significant effect on Job Satisfaction. (3) Transformational Leadership Style has a positive and insignificant effect on Employee Performance. (4) Workload has a positive effect on employee performance. (5) Job satisfaction has a positive and significant effect on employee performance. (6) Transformational Leadership Style has a positive and significant effect on Employee Performance through Job Satisfaction. (7) Workload has a positive and significant effect on employee performance through job satisfaction.